"COMPARISON OF ACUTE MYOCARDIAL INFARCTION RISK FACTORS IN YOUNG AND ELDERLY PATIENTS- A CLINICO-EPIDEMIOLOGY STUDY" - ROHIT KUMAR SRIVASTAVA,; PRATIBHA SINGH,; ARTI VERMA,; SUNITA TIWARI, (International Journal of Pharma and Bio Sciences, 2015)
Acute myocardial infarction (AMI) in young adults is typical as regards risk factors, clinical, angiographic and prognostic characteristics. In young people the risk factor pattern is different from older people. In the present study, we compare and study the clinical presentation, treatment and outcome in young and elderly AMI patients. Total number of 511 AMI patients enrolled and divided into two groups (Group I- ≤45 years old and Group II- >45 years old). The standardized questionnaire was filled seeking information of clinical presentation at hospital admission, in-hospital management, and in-hospital prognosis. A total number of 123 patients were younger than 45 years. The symptom of Killip Class IV (p=0.02), history of hypertension (p=0.02), previous history of coronary artery disease (CAD) (p=0.003) and overweight (p=0.0001) was significantly higher in young patients. The habit of smoking was about four times significantly higher among the subjects of Group I than Group II (RR=3.91, 95%CI=2.31- 6.62, p=0.0001). This study concludes that young patients with AMI differ from older patients in their clinical presentation, past medical history, and outcome.